IMPLEMENTASI METODE ROLE PLAYING PADA MATA KULIAH PELAJARAN PAI - Sayekti, Siskha Putri; Putri, Aida (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
This research is motivated by the obstacles of teachers in providing PAI lessons, namely: 1) the learning model provided is still monotonous, 2) learning is still a teacher-centered, 3) the time allocation is very limited. The formulation of the problem in this paper is how to apply the role playing method in PAI subjects. The purpose of this study is the implementation of the role playing method in PAI subjects. This writing uses a descriptive qualitative method as the object under study is a complex interaction process, namely the process of applying the role playing method in Islamic Religious Education subjects at MA Islamiyah. In the role playing method, students are very actively involved in the learning process doing assignments by making videos. Students will act out a situation related to the material being studied. So, with this role playing method, students are expected to be able to understand the perceptions found in everyday life.